2015
DOI: 10.1093/ijnp/pyv049
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trials of Add-On Antidepressants in Schizophrenia

Abstract: Background:Despite adequate treatment with antipsychotics, a substantial number of patients with schizophrenia demonstrate only suboptimal clinical outcome. To overcome this challenge, various psychopharmacological combination strategies have been used, including antidepressants added to antipsychotics.Methods:To analyze the efficacy of add-on antidepressants for the treatment of negative, positive, cognitive, depressive, and antipsychotic-induced extrapyramidal symptoms in schizophrenia, published randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 86 publications
(138 reference statements)
1
27
0
1
Order By: Relevance
“…To identify any further studies and additional data, we contacted pharmaceutical companies manufacturing antidepressants, sent e-mails to corresponding authors of all included studies for which data were missing, and searched the reference lists of included studies and of previous reviews (1,19,(22)(23)(24)(26)(27)(28)(29). We included randomized controlled trials involving 1) people with schizophrenia or schizophrenia (-like) psychosis (e.g., schizophreniform and schizoaffective disorders), irrespective of the diagnostic criteria used, 2) people treated with any add-on antidepressants marketed in at least one country, administered by any mode (oral tablets, oral liquid) and at any dose, and 3) people treated with any antipsychotics (any dose or mode of administration).…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…To identify any further studies and additional data, we contacted pharmaceutical companies manufacturing antidepressants, sent e-mails to corresponding authors of all included studies for which data were missing, and searched the reference lists of included studies and of previous reviews (1,19,(22)(23)(24)(26)(27)(28)(29). We included randomized controlled trials involving 1) people with schizophrenia or schizophrenia (-like) psychosis (e.g., schizophreniform and schizoaffective disorders), irrespective of the diagnostic criteria used, 2) people treated with any add-on antidepressants marketed in at least one country, administered by any mode (oral tablets, oral liquid) and at any dose, and 3) people treated with any antipsychotics (any dose or mode of administration).…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…Should they be administered during the acute episode or exclusively in the postpsychotic phase? Recent narrative reviews did not answer these crucial questions and delivered unclear conclusions (1,19,20). Crucially, previous systematic reviews and meta-analyses addressed only specific subgroups of patients with schizophrenia or particular adjunctive medications (cognitive impairment [21], negative symptoms [22][23][24][25], postpsychotic depression [26], add-on noradrenergic and specific serotonergic antidepressants ajp in Advance ajp.psychiatryonline.org 1…”
mentioning
confidence: 99%
“…As already mentioned in the introduction, the value of antidepressant treatment is discussed controversially, and current results from clinical and controlled studies are inconsistent [5,11,50]. In their naturalistic study on concomitant medication in 53 tapers, improvements in 3, and worsening in 1, concluding that the efficacy of concomitant antidepressant treatment is limited [51]. Längle et al studied the effects of polypharmacy on outcome in 374 patients with schizophrenia and schizoaffective disorder in routine psychiatric treatment before discharge and after 6, 12, 18, and 24 months of follow-up and found 16 % of the patients receiving antipsychotics combined with antidepressants with less improvement in the non-monotherapy patients [52].…”
Section: Efficacy and Outcomementioning
confidence: 99%
“…Längle et al studied the effects of polypharmacy on outcome in 374 patients with schizophrenia and schizoaffective disorder in routine psychiatric treatment before discharge and after 6, 12, 18, and 24 months of follow-up and found 16 % of the patients receiving antipsychotics combined with antidepressants with less improvement in the non-monotherapy patients [52]. Also, in a very recent review of 36 randomized controlled trials, the vast majority of publications reported no favorable effect of add-on antidepressants on the schizophrenia symptom domains [53].…”
Section: Efficacy and Outcomementioning
confidence: 99%
“…Even though partially beneficial, antipsychotics do not have a satisfying effect on alleviation of the negative symptoms and no drug has received Food and Drug Administration (FDA) approval for treatment of these symptoms [5]. In this regard, the efficacy of antidepressant agents has also been studied in these patients with as yet inconclusive results [6]. Aside from pharmacotherapy, cognitive behavioral therapy is also recommended for the management of negative symptoms but is only moderately effective in these patients.…”
mentioning
confidence: 99%